The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12889-020-8441-2
|View full text |Cite
|
Sign up to set email alerts
|

How does a targeted active labour market program impact on the well-being of the unemployed? A concept mapping study on Barcelona “Employment in the Neighbourhoods”

Abstract: Background: The "Employment in the neighbourhoods" program is an innovative, tailor-made Active Labour Market Program that has been implemented in 12 neighbourhoods in Barcelona (Spain). Its goal is to get people from deprived, high-unemployment neighbourhoods back to work. The aim of this study was to describe the effects of the program on participants' quality of life, and identify the mechanisms underlying these effects, according to their own perception and the perception of technical staff who assisted th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In terms of health and well-being, researchers argue that ALMPs should mitigate the negative effects of unemployment through various psychosocial mechanisms and thus improve health and quality of life (e.g. Puig-Barrachina et al, 2020). One of the most influential theories is Jahoda's latent deprivation theory, according to which employment fulfils various psychological needs (Jahoda, 1982).…”
Section: Discussion and Implications For The Post-pandemic Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of health and well-being, researchers argue that ALMPs should mitigate the negative effects of unemployment through various psychosocial mechanisms and thus improve health and quality of life (e.g. Puig-Barrachina et al, 2020). One of the most influential theories is Jahoda's latent deprivation theory, according to which employment fulfils various psychological needs (Jahoda, 1982).…”
Section: Discussion and Implications For The Post-pandemic Periodmentioning
confidence: 99%
“…Not only do such contractual arrangements play a noticeable role in defining the employment status of a worker, but also in many cases their active labour market policy eligibility (Romero & Kuddo, 2019). There are not only economic barriers young unemployed people face in the labour market, but also social barriers such as social exclusion, poverty, discrimination, and poor mental health (Puig-Barrachina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By instituting active labor market programs (ALMPs), the negative health outcomes associated with unemployment may be effectively addressed, alleviating the adverse health effects brought about by economic recessions [11,71]. To give an example, Reeves et al (2015) found that increasing ALMP expenditure reduce suicide risks [72], and Mattei et al 2019 concluded that ALMPs are effective in softening the association between unemployment and suicide among men, in particular between the ages of 45 to 54 [73].…”
Section: Plos Onementioning
confidence: 99%